Human rights in patient care and public health-a common ground - Maya Peled-Raz (Frontiers Media S.A., 2017)
Abstract Medical law and public health law have both served extensively as instruments of health protection and promotion-yet both are limited in their effect and scope and do not sufficiently cover nor supply a remedy to systematic, rather than anecdotal, mistreatments in the health care system. A possible solution to this deficiency may be found in the human rights in patient care legal approach. The concept of human rights in patient care is a reframing of international human rights law, as well as constitutional thought and tools, into a coherent approach aimed at the protection and furthering of both personal and communal health. It applies human rights discourse and human rights law onto the patient care setting while moving away from the narrow consumeristic view of health care delivery. By applying human rights in patient care approach, both national and international courts may and should serve as policy influencing instruments, protecting the rights of the most vulnerable and prejudiced against groups, which are want of a remedy through traditional patients' rights legal schemes.